2019
DOI: 10.1186/s12859-019-3172-z
|View full text |Cite
|
Sign up to set email alerts
|

MLW-gcForest: a multi-weighted gcForest model towards the staging of lung adenocarcinoma based on multi-modal genetic data

Abstract: BackgroundLung cancer is one of the most common types of cancer, among which lung adenocarcinoma accounts for the largest proportion. Currently, accurate staging is a prerequisite for effective diagnosis and treatment of lung adenocarcinoma. Previous research has used mainly single-modal data, such as gene expression data, for classification and prediction. Integrating multi-modal genetic data (gene expression RNA-seq, methylation data and copy number variation) from the same patient provides the possibility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Many attempts have been made to investigate the incidence, growth, diagnosis and treatment of LUAD. 41 , 42 , 43 , 44 Common histopathological features of stage, tumor size and Karnofsky Performance Status (KPS) are now still considered to be the most important prognostic factors in LUAD. Based on their pathological characteristics, LUAD patients are grouped into different groups to accept the corresponding care regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Many attempts have been made to investigate the incidence, growth, diagnosis and treatment of LUAD. 41 , 42 , 43 , 44 Common histopathological features of stage, tumor size and Karnofsky Performance Status (KPS) are now still considered to be the most important prognostic factors in LUAD. Based on their pathological characteristics, LUAD patients are grouped into different groups to accept the corresponding care regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Predicting NSCLC subtypes by identifying specific genotypes is a potentially powerful method that can be recommended as a special marker for IHC-stained slides. Therefore, several references determined the sensitivity and specificity of genetic markers to discriminate the subtypes of NSCLCs, as shown in Table 2 (31)(32)(33)(34)(35)(36)(37). A retrospective study selected the genetic features from 77 ADCs and 73 SCCs to construct the support vector machine (SVM) and random forest (RF) classifier (32).…”
Section: Diagnosing Histologic Subtypes Of Nsclcs Based On Digital Histopathologic Slides and Gene Profilesmentioning
confidence: 99%
“…Furthermore, with the RNA-seq, methylation data, and copy number variation (CNV) of 369 ADCs from TCGA, Dong et al (36) developed the MLW-gcForest model, a machine learning-based ensemble algorithm, which achieved better classification performance in ADC staging (accuracy, 0.908; precision, 0.896; recall, 0.882; F1, 0.889) incorporating multi-modal data compared with single-modal data. Dong et al (36) indicated that MLW-gcForest integrating multimodal genetic data effectively improved the accuracy of ADC staging, which was significantly superior to the traditional machine learning algorithms. Generally, gene mutations play a critical role in tumor progression and tumor phenotypes.…”
Section: Predicting Pathologic Stages Of Nsclcs Based On Gene Profilesmentioning
confidence: 99%
“…It has been shown that gcForest has much fewer parameters in comparison to DNN and can work well even when there are only small-scale data available. A multi-weighted gcForest has been proposed and developed as a staging model of lung adenocarcinoma based on multi-modal genetic data which could be used for the diagnosis and personalized treatment of lung cancer [ 163 ].…”
Section: Challenges and Future Trendsmentioning
confidence: 99%